Deterioro cognitivo y su afectación el contexto psicosocial de un adulto mayor de 67 años de Mata de Cacao - Villegas Coello, Saul Alexander (2023)
During the period of life of the human being, it goes through several stages of development, being old age the last one that it goes through, during this stage a significant change occurs at the neurological and psychological level called cognitive deterioration, generating great repercussions in the central nervous system, causing decrease in specific neurotransmitters, generating a predisposition to physical and mental illnesses, producing deterioration in memory, attention, orientation, executive functions, thought and language, in addition to impacting the psychosocial context of the individual, mainly because cognitive deterioration in the elderly causes dependency in other people (relatives, friends or caregivers), therefore it is intended to study the issue of cognitive impairment and its affectation in the psychosocial context of an adult older than 67 years of Mata de Cacao, which aims to determine the impact of cognitive impairment in the psychosocial context of an adult over 67 years and which will be carried out through the application of collection techniques such as; observation, interview, bibliographical review, clinical history and application of psychometric tests such as MOCA and the Blessed, Timlison and Roth dementia scale, information that will be organized and specified through the sessions, findings where the diagnosis of F00.1 is proposed. Dementia in late-onset Alzheimer's disease, and as proposed solutions, the cognitive rehabilitation methodology is established to reduce or slow down the deterioration process, concluding that the objective of the investigation was achieved.